Biventricular takotsubo syndrome with COVID-19 in an Asian male. Issue 1 (July 2021) - Fujisaki, Tomohiro; Kassim, Frida; Kassim, Gassan; Bandyopadhyay, Dhrubajyoti; Singh, Vasundhara; Kim, Bette
Abstract: Coronavirus disease 2019 (COVID-19) has been shown to affect the cardiovascular system, and several cases of takotsubo syndrome (TTS) induced by COVID-19 have been reported. TTS predominantly affects postmenopausal women in western countries, but the prevalence in men is higher in Asian populations. It should be noted that male patients with either TTS or COVID-19 are associated with higher mortality. Despite the higher prevalence of TTS in Asian men, little is known about Asian men with TTS induced by COVID-19. This is a case report of a 60-year-old Asian male with biventricular TTS precipitated by COVID-19. He presented with acute respiratory distress syndrome, cardiogenic shock, and acute kidney injury. He required intubation, multiple vasopressors, and renal replacement therapy. The left ventricular ejection fraction was 15%, but it normalized in 5 weeks. The patient had a prolonged hospital stay in a critical condition, but was eventually discharged alive. The scarce literature about this condition in Asian male populations and the increasing number of COVID-19 cases in Asian countries highlight the rarity and importance of this case. Further studies are warranted to investigate the uneven sex distribution and outcomes of TTS triggered by COVID-19 in an Asian population. <Learning objective: Takotsubo syndrome (TTS) can be provoked by coronavirus disease 2019 (COVID-19). Male sex, right ventricular dysfunction, and COVID-19 as a trigger, are important predicting factors for worse prognosis. It is unknown if there is a significant racial difference in the sex distribution and outcomes for this condition. Further studies are warranted to investigate TTS triggered by COVID-19 in an Asian population.>